Korelasi Blood Flow Rate Intraoperasi dan Enam Minggu Pascaoperasi Arteriovenous Fistula Brakiosefalika Dihubungkan dengan Maturitas di RSUP Prof. Dr. R. D. Kandou Manado - Palin, Aubrey W.; Tjandra, Djony E.; Sumangkut, Richard M. (Jurnal Biomedik : JBM, 2019)
Abstract: American National Kidney Foundation (2002) states that end-stage kidney disease is an indication for renal replacement therapy, one of which is hemodialysis. Vascular access comprises a fundamental component of hemodialysis therapy (HD), facilitating the patient’s blood flow to the dialyzer. However, there are some factors affecting the maturity of an arteriovenous fistula (AVF), inter alia the patient, comorbidities, and anatomical and functional conditions of the blood vessels involving the blood flow rate (BFR). This study was aimed to establish the differences between intra-operative BFR and BFR six weeks after surgery as well as any correlations between intraoperative BFR, venous diameter, and skin to vein distance with maturity of brachiocephalic AVF. This was prospective cohort study conducted at the Department of Surgery, Prof. Dr. R. D. Kandou General Hospital Manado. Subjects were 41 CKD patients who underwent brachiocephalic AVF surgery. The vein diameter, skin to vein distance, and BFR were measured immediately as intra-operative data using a Doppler USG and all were re-measured at six-week-follow-up examination as six-week-postoperative data. The results showed that there was a significant increase in BFR at six weeks postoperation compared to intraoperation (t=-19.215; P <0.0001). Bi-serial point correlation analysis revealed that there was a significant correlation between intraoperative venous diameter and maturity (rpb=0.276; P=0.04) as well as a significant correlation between intraoperative BFR and maturity (rpb=0.615; P=0.002). No significant correlation was observed between intra-operative skin to vein distance and maturity (rpb=0.093; P=0.281). Conclusion: There was a significant difference in BFR between intraoperation and 6 weeks postoperation in the mature AV fistula. There was a significant relationship between intraoperative BFR and maturity as well as between intraoperative venous diameter and maturity, while no significant relationship between skin-vein distance and maturity was found.Keywords: brachiocephalic AVF, BFR, maturityAbstrak: American National Kidney Foundation (2002) menyatakan bahwa penderita dengan penyakit ginjal tahap akhir diindikasikan untuk dilakukan terapi pengganti ginjal, salah satunya hemodialisis (HD). Akses vaskular merupakan komponen penting pada terapi HD karena melalui akses vaskular darah dari tubuh pasien dapat dialirkan menuju dialyzer. Terdapat banyak faktor yang memengaruhi maturitas suatu arteriovenous fistula (AVF), yaitu pasien itu sendiri, komorbid, serta keadaan anatomi dan fungsional pembuluh darah termasuk nilai blood flow rate (BFR). Penelitian ini bertujuan untuk mengetahui perbedaan BFR intraoperasi dan BFR enam minggu pascaoperasi serta adanya korelasi antara BFR intraoperasi, diameter vena, dan jarak kulit-vena dengan maturitas AVF brakiosefalika. Penelitian ini dilaksanakan di Bagian Bedah RSUP Prof. Dr. R. D. Kandou Manado dengan desain kohort prospektif. Subyek penelitian ialah 41 pasien PGK yang menjalani operasi pembuatan AVF brakiosefalika. Setelah selesai operasi dihitung diameter vena, jarak kulit-vena, dan BFR sebagai data intraoperasi menggunakan USG Doppler. Penghitungan dilakukan kembali 6 miggu pascaoperasi. Hasil penelitian mendapatkan peningkatan BFR yang sangat bermakna pada enam minggu pascaoperasi dibandingkan intraoperasi (t =-19,215, P<0,0001). Dengan analisis korelasi point biserial didapatkan hubungan bermakna antara diameter vena intraoperasi dengan maturitas (rpb=0,276; P=0,04), tidak terdapat hubungan bermakna antara jarak kulit-vena intraoperasi dengan maturitas (rpb=0,093; P=0,281), dan terdapat hubungan bermakna antara BFR intraoperasi dengan maturitas (rpb=0,615; P=0,002). Simpulan: Terdapat perbedaan bermakna antara BFR intraoperasi dan BFR 6 minggu pascaoperasi pada AVF matur. Terdapat hubungan bermakna antara BFR intraoperasi dan diameter vena intraoperasi dengan maturitas namun tidak terdapat hubungan bermakna antara jarak kulit-vena dengan maturitas.Kata kunci: AVF brakiosefalika, BFR, maturitas